Efecto de tres fuentes y tres dosis de compost con aplicación de microorganismos eficaces en el desarrollo y rendimiento de Pepinillo Híbrido, (Stomewall-F1) en la provincia de Lamas-departamento de San Martín - Santa Cruz Carhuajulca, Noé (2011)
This research paper entitled ¨ Effect of three sources and three rates of compost application of effective microorganisms in the development and performance of hybrid cucumber (STOMEWALL - F1) in the province of Lamas, San Martín Department ¨, which were tested 3 sources and 3 doses of compost used as sources: poultry, and cows whose dose of 10, 15 and 20 Tn.ha-1 and application of Effective Microorganisms (EM), was used randomized complete block design with factorial arrangement of 3 x 4, with 4 replicates and 12 treatments for combinations of sources and doses plus a control without fertilization. Based on the results and the discussions in this work was reached the following conclusions: the source of credit with better answers about the development of the pickle was the compost of which, who projected significant differences above the cows and Compost manure on plant height, number of fruits per plant, fruit length, fruit diameter, fruit weight and yield of cucumber in hundreds of treatment; about composting doses were doses of 20 and 15 tons. defined ha-1 the best results for plant height, number of fruits per plant, fruit length, fruit diameter, fruit weight; cucumber yield hundreds per treatment and treatments T7 (whose x 15 Tn.ha-1) and T6 (whose x 20 Tn.ha-1) with averages of 11 052.5 and 10 543.75 exceeded hundreds of pickles the other treatments, with treatments T4, T8 and T12 (witnesses) who threw the lower performance in hundreds of pickles with an average of 8371.66 and analysis Benefit / Cost defined the T6 (whose x 15 Tn.ha-1) as the best treatment with a value of 5.47, followed by T1 (chicken Tn.ha x10-1), T5 (whose x10 Tn.ha-1) and T7 (Cuyasax20 Tn.ha-1) who reached values of 5.39, 5.39 and 5.38 respectively. Since this preliminary conclusion, it is assumed better results in subsequent crops due to increased compost applied treatments and insufficient time for the minerals were fully available to plants.